Molecular characterisation of the vibrio midae SY9 extra cellular alkaline serine protease and its role in the previously observed probiotic effect on the growth of Haliotis midae - Huddy, Robert John (Department of Molecular and Cell Biology, 2014)
Abalone are marine gastropods that command a very high market price, particularly in the Far East where they are a highly sought after sea food delicacy. South Africa has a rapidly developing abalone aquaculture industry, based on the cultivation of Haliotis midae in landbased race-way systems. The relatively slow growth rates of abalone represent a major constraint on the abalone aquaculture industry. However, there is mounting experimental evidence showing that the health and physiology of aquacultured species can be improved through the prophylactic use of probiotic bacteria. Previous research by Macey and Coyne (2005) showed that H. midae fed a high protein artificial diet, ABFEED(R) S34, supplemented with the bacterium Vibrio midae SY9 have enhanced digestion, growth and immune responses. Probiotic microorganisms are thought to function in a variety of ways, which include the secretion of extracellular enzymes that may enhance digestion in the host organism. However, most of the investigations conducted on probiotic microorganisms for aquacultured species have failed to elucidate the exact mode of action. In this study, the predominant V. midae SY9 extracellular alkaline protease, VmproA, was investigated in an attempt to determine the role of VmproA in the growth enhancing probiotic effect observed by Macey and Coyne (2005) for abalone fed V. midae SY9 supplemented feed. The V. midae SY9 gene, vmproA, encoding the protease was cloned from a previously constructed genomic library and characterised. Nucleotide sequencing and analysis indicated that vmproA encodes a protein, VmproA, which has high similarity to a Vibrio alginolyticus extracellular detergent resistant alkaline serine protease. Furthermore, during the course of this investigation it became apparent that VmproA may represent an extracellular alkaline detergent-stable, member of the proteinase K-like subfamily of the subtilase superfamily of serine proteases. The detergent-stable protease gene, vmproA, was targeted for gene mutagenesis through vmproA gene duplication and disruption, resulting in the construction of the mutant strains V. midae SY9Pro2 and V. midae SY9Mut2, respectively. VmproA gene duplication and disruption did not significantly influence the growth of the mutant strains in batch culture in comparison to V. midae SY9. V. midae SY9Pro2 produced and secreted VmproA and had equivalent levels of extracellular protease activity to V. midae SY9 when cultivated in a high protein medium. However, insertional inactivation of vmproA resulted in a loss of VmproA production and secretion. This also resulted in a significant reduction in the extracellular protease levels produced by V. midae SY9Mut2 in comparison with that of V. midae SY9. The effect of dietary supplementation with either V. midae SY9, V. midae SY9Pro2 or V. midae SY9Mut2 on H. midae growth performance was investigated in a growth trial. The basal diet of ABFEED(R) S34 weaning chips was separately supplemented with the V. midae SY9 strains by vacuum impregnation so as to achieve a viable cell concentration of greater than 108 CFU g-1 ABFEED(R). After 180 days, H. midae receiving either the V. midae SY9Pro2 or V. midae SY9Mut2 supplemented diets displayed significantly (P<0.05) enhanced growth parameters compared to abalone fed either the basal diet or the V. midae SY9 supplemented diet. However, there was no significant difference (P>0.05) between animals fed the V. midae SY9 supplemented diet or the control diet. In situ alkaline protease levels within the crop/stomach and intestinal digestive tract regions were significantly enhanced (P<0.05) in H. midae fed V. midae SY9 supplemented ABFEED(R) S34 compared to animals fed the basal diet or the basal diet supplemented with either V. midae SY9Pro2 or V. midae SY9Mut2. In situ hybridization and immunohistochemistry were employed to examine the in vivo localisation of dietary supplemented V. midae SY9 cells and VmproA within the H. midae digestive tract. V. midae SY9 was chromosomally tagged with the mini-Tn10-gfp-kan transposon and the resulting strain, V. midae SY9